Danggui Buxue Tang, a Chinese Herbal Decoction Containing Astragali Radix and Angelicae Sinensis Radix, Modulates Mitochondrial Bioenergetics in Cultured Cardiomyoblasts - Kwan, Kenneth K.L.; Huang, Yun; Leung, Ka W.; Dong, Tina T.X.; Tsim, Karl W.K. (Frontiers in Pharmacology, 2019)
Danggui Buxue Tang (DBT) is an ancient herbal mixture containing Astragali Radix and Angelicae Sinensis Radix, and which are commonly consumed for “qi-invigorating” (i.e., stimulating vital energy/energy metabolism) as traditional Chinese medicine (TCM). The pharmacological activities of DBT in anti-oxidation, estrogenic, hematopoietic, and immunogenic have been reported; however, the role of DBT in cellular energy metabolism has not been determined. Here, we employed an extracellular flux analyzer to evaluate the mitochondrial respiration of cultured H9C2 cardiomyoblasts in present of DBT. The herbal extract of DBT was qualified chemically for the major ingredients, i.e. astragaloside, calycosin, formononetin, Z-ligustilide, and ferulic acid. The anti-oxidant activities of DBT, as well as its major ingredients, were determined by Folin-Ciocalteu assay, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, and protective effect in tert-butyl hydroperoxide (tBHP)-treated cultured cardiomyoblasts. In addition, a real-time oxygen consumption rate (OCR) in herbal extract-treated cultured cardiomyoblasts was revealed by using a Seahorse extracellular flux analyzer. In addition, the transcript expressions of peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PCG-1α) and other genes relating to mitochondria biogenesis were determined in cardiomyoblasts under different herbal treatments. DBT possessed the strongest anti-oxidant activity and protective effects on the oxidatively stressed cardiomyoblasts. By revealing the OCR in mitochondria, the health state of cultured cardiomyoblasts under DBT was improved via increase of basal respiration, proton leak, non-mitochondria, and adenosine triphosphate (ATP) production. Furthermore, the transcriptional activities of genes responsible for mitochondrial biogenesis and DNA replication were stimulated by application of DBT in cultures.